Using social media to analyze public psychological status during the recovery period of COVID-19 in China - Jia, Fei (J Public Health (Oxf), 2020)
BACKGROUND: During the outbreak, billions of people were eager to get information about COVID-19 through social media. Social media can not only deliver reliable information to the public but can in turn reflect changes in the public’s psychological status. Insight into the public’s hotspots of concern and mental status through media background tools contributes to the formulation of public health policies and the clarification of epidemic development mode. METHODS: WeChat is the largest social media in China. Taking the recovery period of COVID-19 in China, for example, we collected WeChat Index data and analyzed the public’s concern about the course of COVID-19 and the restoration of emotional tendency through keywords search. RESULTS: With the gradual control of the COVID-19 in China, the public psychological status changes from negative to neutral, accompanied by a weakening of negative emotions and an increase in positive emotions. Every obvious inflection point of improvement in social operation is reflected in the increase of public attention and the relaxation of lifestyle. CONCLUSIONS: Social media can be used to monitor the public psychological status and the development mode and trend of infection in one country during a pandemic.